2023
DOI: 10.1002/cre2.720
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of push‐out bond strength of endodontic sealers after root canal drying with different techniques

Abstract: Objectives An ideal endodontic sealer should bond to both dentin and root‐filling material. This study aimed to assess the push‐out bond strength (PBS) of mineral trioxide aggregate (MTA)‐Fillapex, Endoseal MTA, AH26, and Sure‐Seal Root to root dentin after root canal drying with different techniques. Materials and Methods This in vitro study was conducted on 160 extracted mandibular premolars. After root canal preparation, the teeth were randomly divided into four grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In the evaluation of bioceramic cements, namely, iRoot SP, MTA Fillapex, Endoseal MTA, and SureSeal Root, it was found that the optimal humidity conditions for achieving ideal strength involved normal humidity using the conventional protocol (paper tips), enhancing the adhesive strength of the sealers [46,49]. Calcium silicate and calcium phosphate in the composition of CSCs rely on humidity for the hydration reaction, allowing the sealer to set and harden [19].…”
Section: Drying Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…In the evaluation of bioceramic cements, namely, iRoot SP, MTA Fillapex, Endoseal MTA, and SureSeal Root, it was found that the optimal humidity conditions for achieving ideal strength involved normal humidity using the conventional protocol (paper tips), enhancing the adhesive strength of the sealers [46,49]. Calcium silicate and calcium phosphate in the composition of CSCs rely on humidity for the hydration reaction, allowing the sealer to set and harden [19].…”
Section: Drying Protocolmentioning
confidence: 99%
“…It is noteworthy that while many studies only assess the sealer to examine the impact of humidity on the bond strength to root dentin, the behavior of these cements in clinical applications, particularly when used in conjunction with gutta-percha cones, should also be considered [19]. Consequently, the careful selection of the drying technique based on the type of cement used emerges as a critical step in endodontic treatment [46].…”
Section: Drying Protocolmentioning
confidence: 99%
See 1 more Smart Citation